2019
DOI: 10.1007/s11664-019-06949-6
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Rotation Rate on Bismuth Saturation in GaAsBi Grown by Molecular Beam Epitaxy

Abstract: GaAs 1Àx Bi x has been grown by solid-source molecular beam epitaxy using varying substrate rotation rates. Changes in local bismuth saturation were studied by varying the Bi/Ga pressure ratio across the wafer. Films were grown on both GaAs and InGaAs buffer layers with varying indium content to change the strain conditions of the bismide layer and the out-of-plane growth rate. All samples demonstrated vertical composition modulations with a period of $ 4 nm that tracked with the rate of growth per substrate r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 34 publications
1
3
0
1
Order By: Relevance
“…A vertical spiral in regards to Bi concentration can be obtained in GaAsBi this way, as has been well explained in M.A. Stevens et al [66]. A cross-sectional HAADF image of the GaAsBi sample S3 is shown in Fig.…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…A vertical spiral in regards to Bi concentration can be obtained in GaAsBi this way, as has been well explained in M.A. Stevens et al [66]. A cross-sectional HAADF image of the GaAsBi sample S3 is shown in Fig.…”
Section: Resultssupporting
confidence: 60%
“…f Horizontally summed vertical X-ray counts profile of the raw As-K and Bi-M signal. Two aligned data sets are combined to obtain the profile [66]. In contrast to samples S1 and S2, the VCM is achieved in S3 by utilizing a slower substrate rotation rate (RPM), which is coupled to intrinsically inhomogeneous elemental flux profiles reaching the substrate in a typical MBE chamber.…”
Section: Resultsmentioning
confidence: 99%
“…Stevens et al made similar observations at 250 °C. [ 123 ] However, it is not yet clear whether this technique can increase the Bi contents accessible at high temperatures, as required for high‐quality device growth. Existing temperature‐limited Bi content predictions are all based on quasiequilibrium growth conditions [ 92,97,104 ] and exceeding these limits through nonequilibrium growth may lead to substantially reduced device dark currents.…”
Section: Prospects For Improving Mbe Growthmentioning
confidence: 99%
“…The large size and low electronegativity of Bi have limited the impact of this alloy and introduced many challenges during the epitaxial growth, such as phase separation [9], surface droplets [10,11], atomic ordering [12][13][14]. To promote the Bi incorporation, the alloy needs to be grown using comparatively lower temperatures, and modified V/III flux ratios [3,[15][16][17][18][19][20][21][22][23][24][25]. By growing at 200 • C using MBE, Lewis et al reported the record high Bi concentration at 22% [20].…”
Section: Introductionmentioning
confidence: 99%